Zentralitätsforschung - ein alter Hut für die Regionalforschung und Raumordnung heute? - Gebhardt, Hans (ERDKUNDE, 1996)
During the 60's and 70's Central Place Theory has developed to a well accepted theory in geography as well as in regional planning. Actually it has taken on more and more the role of an old shoe in regional policy; central places receive updates in regional plans, but there is no update in the theory which could make allowances for the structural changes in producer and consumer services as well as in social behaviour. Its an unsolved problem, especially for geographers thanks to Walter Christaller and his long established theory. A number of actual necessities in research exists: how to combine the Central Place Theory with concepts of indigenous development, how to evaluate the role of business related services, how to integrate the modem consumer behaviour in a post-fordist society , how to develop a new model which takes into consideration new social standards, as for example energy conservation or traffic reduction. There is a need for further discussion and development of the Central Place Theory, as well as the integration of social behaviour into empirical research. We must develop concepts and guidelines far the future development of retail trade locations and services as well as for the moderation of development processes.